The Associations of Arterial Stiffness and Central Hemodynamics with Carotid Atherosclerosis in Patients at a High Coronary Risk: A Cross-Sectional Study - Hack-Lyoung Kim; Soonil Kwon; Hyun Sung Joh; Woo-Hyun Lim; Jae-Bin Seo; Sang-Hyun Kim; Joo-Hee Zo; Myung-A Kim (Pulse)
Introduction: It is not well-known which indicator, central blood pressure (CBP) or arterial stiffness, has a greater impact on carotid atherosclerosis. This study aimed to assess the associations of carotid atherosclerosis with arterial stiffness and CBP in the same individuals. Methods: A total of 142 patients (mean age: 69 years; 43% female) with documented atherosclerotic cardiovascular disease or multiple risk factors were analyzed. Brachial-ankle pulse wave velocity (baPWV) and CBP measurements, along with carotid ultrasound, were performed on the same day. CBP was assessed using radial artery tonometry. Results: In simple linear regression analysis, only baPWV exhibited a significant correlation with carotid intima-media thickness (CIMT) (r = 0.272; p = 0.001), whereas none of the CBP parameters (systolic, diastolic, pulse pressures, and augmentation index) correlated with CIMT (p > 0.05 for each). Multiple linear regression analysis indicated that baPWV had no significant association with CIMT after adjusting for age (p = 0.264). A higher baPWV (≥1,656 cm/s) was significantly associated with carotid plaque presence, even after accounting for potential confounders (odds ratio: 3.66; 95% confidence interval: 1.65–8.12; p = 0.001). Moreover, as the number of carotid plaques increased, there was a linear rise in baPWV (p < 0.001). None of CBP parameters were associated with the presence of carotid plaque (p > 0.05 for each). Conclusions: Among a high-risk Korean population, baPWV demonstrated a stronger association with carotid plaque presence and extent compared to CBP parameters. Thus, baPWV may serve as a valuable marker for identifying carotid plaque.